2019
DOI: 10.1002/cbic.201900272
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Gene Circuit Parts Based on Multiobjective Optimization by Using Standard Calibrated Measurements

Abstract: Standardization and characterization of biological parts is necessary for the further development of bottom‐up synthetic biology. Herein, an easy‐to‐use methodology that embodies both a calibration procedure and a multiobjective optimization approach is proposed to characterize biological parts. The calibration procedure generates values for specific fluorescence per cell expressed as standard units of molecules of equivalent fluorescein per particle. The use of absolute standard units enhances the characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…There is also a gap between calibration in terms of equivalent dye molecules and the ability to interpret these numbers in terms of the actual fluorescent protein used, as illustrated by the high degree of variation between channels in Figure 6(c−d). Shifting units from equivalent dye molecules to protein molecules (e.g., by adaptation of methods based on spectral information 32 or protein purification 33 ) would also address the problem of channel-to-channel conversion, though in some circumstances this can also be handled by multicolor controls, as has been previously shown. 5,34 Beyond flow cytometry, it will be important establish that other measurement modalities can also achieve the requisite level of measurement precision.…”
Section: ■ Discussionmentioning
confidence: 99%
“…There is also a gap between calibration in terms of equivalent dye molecules and the ability to interpret these numbers in terms of the actual fluorescent protein used, as illustrated by the high degree of variation between channels in Figure 6(c−d). Shifting units from equivalent dye molecules to protein molecules (e.g., by adaptation of methods based on spectral information 32 or protein purification 33 ) would also address the problem of channel-to-channel conversion, though in some circumstances this can also be handled by multicolor controls, as has been previously shown. 5,34 Beyond flow cytometry, it will be important establish that other measurement modalities can also achieve the requisite level of measurement precision.…”
Section: ■ Discussionmentioning
confidence: 99%
“…This is strongly supported by the results of Volkmer and colleagues (Volkmer and Heinemann, 2011) whose data suggests this variation is within ∼2-fold across a wide range of growth conditions, but also by others who have shown that as cell volumes increase, their OD-specific cell counts decrease by approximately the same magnitude (Schaechter et al ., 1958; Basan et al ., 2015). Units of concentration may also be more meaningful for reaction modelling since ultimately it is molecular concentration that is critical for binding and kinetics (Bloom et al ., 2014; Siegal-Gaskins et al ., 2014; Boada et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This is only possible if RFUs from both FPs can be separately converted into molecular units of protein. Some have attempted to tackle this by attempting to predict the relative brightness of FPs using theoretical values (Boada et al, 2019;Vignoni et al, 2019), but such calibrations make a number of unvalidated assumptions, for instance about translation rate equivalence across constructs, that require rigorous testing before they can be adopted.…”
Section: Introductionmentioning
confidence: 99%
“…Note that results are not particularly sensitive to the tolerance constant of 1.5 (used also in ( 4 ) and ( 3 )), as the absolute maximum pipetting error β found for any sequence is just over 10%. Note also that a potential alternative model substitutive instrument non-linearity for pipetting bias can be found in ( 6 ).…”
Section: Methods: Unit Scaling Factor Computationmentioning
confidence: 99%